The house next door eaudiobook - Patterson, James (2019)
An affair spirals out of control, a detective investigates four mysterious disappearances, and a mysterious message from space leads to a manhunt in these three electrifying thrillers from the world's #1 bestselling writer. The House Next Door (with Susan DiLallo): Married mother of three Laura Sherman was thrilled when her new neighbor invited her on some errands. But a few quick tasks became a long lunch — and now things could go too far with a man who isn't what he seems . . . The Killer's Wife (with Max DiLallo): Four girls have gone missing. Detective McGrath knows the only way to find them is to get close to the suspect's wife . . . maybe too close. We. Are. Not. Alone. (with Tim Arnold): The first message from space will change the world. It's first contact: undeniable proof of alien life. Disgraced Air Force scientist Robert Barnett found it. Now he's the target of a desperate nationwide manhunt — and Earth's future hangs in the balance.